Analysis of Misdiagnosis of 4 Cases of Tuberculosis of Thyroid and Literature Review. (27th December 2012) - Yin, De-Tao; Wu, Wenxun; Cao, Shengli; Li, Hongqiang
Abstract : Objective . To investigate the cause of misdiagnosis and the diagnosis and treatment of tuberculosis of thyroid. Methods . Four cases of tuberculosis of thyroid were reported and the related literature was reviewed, as well as the causes of misdiagnosis and the diagnosis and treatment were discussed. Results . Two cases were misdiagnosis as thyroid adenoma and one case as thyroid carcinoma, while one case as missed diagnosis. Part of resection, local excision, and lobectomy was performed, respectively, with all the patients who were treated with antituberculosis drugs and recovered. Conclusion . The atypical manifestation of tuberculosis of thyroid suggested that it is important to reinforce the knowledge of this disease. Cytological examination by fine-needle aspirate biopsy was helpful to the diagnosis. The first choice was treatment with anti-tuberculosis drugs.